KONSTRUKSI TES UNTUK MENGUKUR HIGHER ORDER THINKING SKILLS PADA MATERI EKOSISTEM KELAS VII - Islami, Rafika Sekar Nur; Sabtiawan, Wahyu Budi (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This study aimed to produce a valid higher order thinking skills assessment instrument in terms of content validity. This study was a type of research and development, following a development model that involves the stages of Planning, Production, and Evaluation (PPE). The question items on the instrument developed refer to the cognitive level of analyzing and evaluating based on Bloom's revised taxonomy. The data collection technique used a questionnaire method in the form of a validation sheet given to an expert lecturer as well as two science teachers. Data from the validation sheet was analyzed using qualitative and quantitative analysis techniques. The results of the data analysis showed that the 9 items that had been developed were declared valid by the three validators in accordance with the recommendations for valid item criteria based on material, construction, and language aspects.